2016
DOI: 10.1097/cmr.0000000000000294
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma masquerading as nonmelanocytic lesions

Abstract: Increased awareness among dermatologists as well as the development of dermoscopy and sequential dermoscopy have contributed significantly toward an increase in the diagnostic accuracy of pigmented melanoma and even of amelanotic melanoma. However, the dermatologist's nightmare is the small group of melanomas that present as common skin diseases, often associated with a significant delay in diagnosis and hence a poor prognosis. The study was carried out to prospectively assess the number of melanomas lacking a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 18 publications
1
16
0
2
Order By: Relevance
“…As reported in literature, a male predominance was noted in our population 1,2 . However, the relationship between gender and AHM remains controversial as other studies showed a female predominance 2,15,16 or neither gender 17 . The median age of our population is comparable to that reported in previous studies 2,9 and in pigmented melanoma 18 .…”
Section: Discussionsupporting
confidence: 56%
“…As reported in literature, a male predominance was noted in our population 1,2 . However, the relationship between gender and AHM remains controversial as other studies showed a female predominance 2,15,16 or neither gender 17 . The median age of our population is comparable to that reported in previous studies 2,9 and in pigmented melanoma 18 .…”
Section: Discussionsupporting
confidence: 56%
“…One limitation to our system (and to other TDS systems) remains the initial triage deciding whether a lesion is to be analyzed or not, which may miss rare clinical presentations such as amelanotic melanoma [ 7 ]. However, the classification of more than 90% of acquisitions as low-priority management indirectly indicates the possibility of an effective screening at PHCs.…”
Section: Discussionmentioning
confidence: 99%
“…Although dermoscopy has steadily increased the diagnostic accuracy of skin cancer, its use is limited in first-line medicine [6,7]. Teledermoscopy (TDS) allows image analysis at a distance.…”
Section: Introductionmentioning
confidence: 99%
“…Entre los diagnósticos diferenciales se mencionan: granuloma piógeno, hemangioma, sarcoma de Kaposi, eccema, nevo melanocítico, queratosis seborreica, verruga vulgar, enfermedad de Bowen, queratoacantoma, carcinomas basocelular y espinocelular, poroma ecrino y algunas infecciones 2,4,12 .…”
Section: Comentariounclassified